Development of an in planta infection system for the early detection of Ganoderma spp. in oil palm - Goh, Kar Mun; Dickinson, Matthew; Alderson, P.; Yap, L.V.; Supramaniam, Christina V. (Italian Phytopathological Society, 2016)
Basal stem rot (BSR) disease caused by the white rot fungus, Ganoderma spp. is a serious threat to the growth and production of oil palm (Elaeis guineensis Jacq.). Traditional in planta infection technique using inoculated rubber wood block can be inaccurate and time-consuming. In this study, a new in planta infection system was developed to detect early symptoms of BSR in young oil palm. One month old clones of oil palm plantlets were artificially infected with pathogenic fungal inoculum (G. boninense GBLS isolate) at three levels of treatments (control, T1; wounded but not infected, T2; wounded and infected, T3) for a period of 8 days. Significant declines in leaf chlorophyll content (from 32.59 to 12.60 SPAD), increases in disease severity index (DSI) values (from 5.56 to 70.37 %) and increased amounts of GBLS DNA (from 0.2 to 116.1 ng μl-1) were progressively detected in T3 as compared to the T1 and T2 plantlets. The internal stem tissues of T3 plantlets were observed to deteriorate gradually from Day 2 post inoculation (DPI) and were severely colonized and damaged by 8 DPI. The potential defence mechanism of total phenolic content peaked on 6 DPI (3.7 mg g-1) in T3 plantlets and reduced thereafter. The data obtained is consistent with BSR symptoms reported in mature oil palm and is indicative of the reproducibility and reliability of an in planta infection system as an effective approach to detect early BSR symptoms in oil palm.